INFLUENCE OF INTRINSIC, EXTRINSIC AND APATHETIC MOTIVATION ON LOCAL COMMUNITY INTENTIONS TO PARTICIPATE IN ECOTOURISM DEVELOPMENT AT KUCHING WETLANDS NATIONAL PARK, SARAWAK, MALAYSIA - Shah K.; Johari S.; Mariapan M.; Alam M.N.; Emang D.; Rosli Z.; Kohdi M. (Forestry Department of Peninsular Malaysia, 2023)
Malaysia is blessed with high potential ecotourism destinations and is committed to explore and develop these destinations under the National Ecotourism Development Plan of Malaysia 2016-2025 for the benefit of the local communities. The role of the local community is pivotal for the success of ecotourism development in such destinations; however, it cannot be achieved without active and motivated community while taking part in the development process. This study aimed to understand the influence of motivation on the intention of the local community to participate in ecotourism development by alluding to theories of motivation and planned behavior. The study was conducted under positivism philosophy, deductive approach, explanatory research design, cross-sectional data, and quantitative methodology for which data was collected from 404 respondents through survey questionnaires. The collected data was analyzed using Smart-PLS 3.2.9 and SPSS 23. The results revealed significant positive effects of both, intrinsic and extrinsic motivation on participatory intentions of local communities. The apathetic motivation nonetheless was found not to be significantly effective in this regard. This study can be used as a tool of motivation for local communities to participate in the ecotourism development especially near wetland parks. The empirical data collected can prove as a useful academic asset in carrying out further scientific studies and initiatives relating to the future of Kuching Wetlands National Park, Sarawak, Malaysia. 2021 Forestry Department of Peninsular Malaysia. All rights reserved.